A minimal bibliometric analysis review on the development of hybrid nanofluids - Bing, Kho Yap; Rahimah, Jusoh (Penerbit UMP, 2023)
The term "hybrid nanofluids" has emerged relatively recently, showcasing significant promise in elevating thermal conductivity while addressing the limitations of mono nanofluids. As of 2023, an extensive body of work, comprising over a thousand published articles on hybrid nanofluids, is accessible in renowned, high-impact-factor journals globally. To provide a comprehensive overview of this research field, this paper employs a bibliometric approach. Data pertaining to publications in the domain of hybrid nanofluids was collected from the Science Direct database, covering the years 2021 to 2023. The search was initiated by employing the query "hybrid nanofluid" in the title, abstract, and keyword search fields, followed by meticulous filtration to precisely extract pertinent articles. Additionally, this study employs VOSviewer software to interpret and analyse aspects such as co-authorship among countries and affiliations, publication citations, and co-occurrence of authors, offering a holistic understanding of the research landscape in hybrid nanofluids.